(untitled) (Research, Society and Development, 2021)
Breast cancer occurs when there is an exacerbated proliferation of cells, that is, a rapid and disordered multiplication of cells that can occur due to environmental and genetic factors. Breast cancer stands out as the second most frequent type of neoplasm worldwide, just behind non-melanoma skin cancer, which occupies the first place. The risk factors that are most linked to the development of breast cancer are advanced age, reproductive characteristics, family history of cancer and lifestyle habits. This is a descriptive study, of the experience report type, carried out in a Basic Health Unit, in Belém, Pará, during an action carried out in that unit on raising awareness in the prevention and treatment of breast cancer. The women who were participating in the conversation circle listened carefully to the reports and explanations in order to perform the ’touch’ on the breasts as a form of early detection, with the intention of seeking medical care when they noticed something abnormal. Multiprofessional care is crucial so that there is a lower incidence of mortality rates caused by breast cancer. Thus, there is a need for training of all professionals in primary care, providing educational actions that clarify the forms of prevention and treatment of breast cancer.